2009
DOI: 10.3329/jbsa.v19i1.4010
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Granisetron, Ondansetron and Metoclopramide in the Prevention and Treatment of Post Operative Nausea and Vomiting after Laparoscopic Cholecystectomy - A Comparative Study

Abstract: SUMMARY:Postoperative nausea and vomiting are the common morbidity after general anaesthesia and surgery 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…8 Forth, Yeasmeen et al found that Granisetron is more effective than Ondansetron in the prevention and treatment of postoperative nausea and vomiting. 13 So Granisetron was preferred over Ondansetron. Regarding the dose of Granisetron, Kamanabrou et al found 40 µg/kg as the optimal dose of Granisetron for chemotherapy induced vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…8 Forth, Yeasmeen et al found that Granisetron is more effective than Ondansetron in the prevention and treatment of postoperative nausea and vomiting. 13 So Granisetron was preferred over Ondansetron. Regarding the dose of Granisetron, Kamanabrou et al found 40 µg/kg as the optimal dose of Granisetron for chemotherapy induced vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies show that ondansetron administration has been more effective than metoclopramide in reducing nausea and vomiting,[ 21 22 ] while others have revealed that the two drugs were not different in control and reduction of nausea and vomiting. [ 15 23 ] In our study, both ondansetron–dexamethasone and metoclopramide–dexamethasone in general decreased the incidence of nausea and vomiting. In a study of 100 patients undergoing laparoscopic cholecystectomy, that was conducted by Mortazavi et al .…”
Section: Discussionmentioning
confidence: 54%
“…[13][14][15] Other published studies that evaluated the efficacy of ondansetron and metoclopramide administered intravenously have shown similar reductions in the incidence of PONV during the 24 h post recovery period. 10,16,17 A study has reported that efficacy (absence of PONV) with ondansetron was 88.6% while with metoclopramide was 57.6% and the results were statistically significant (P<0.05). 2 Another study supported these results and reported that efficacy of ondansetron was 69% while with metoclopramide was 44% and the results were statistically significant (P<0.05).…”
Section: Discussionmentioning
confidence: 99%